Vilnius and Urban Planning Threads in the Pre-war Texts of Józef Mackiewicz - Krupowies, Walentyna (Slavistica Vilnensis, 2024)
The article points out the dominant themes of Józef Mackiewicz's pre-war work, indicates Vilnius as one of the main goals of Mackiewicz's writing, and analyses selected pre-war columns and reportages,  primarily the diptych Z wileńskiego bruku (From the Vilnius Pavement) and a series of reportages under the common title Poszukiwania tajemniczego portcygaru w Wilnie (Search for the Mysterious Portcygar in Vilnius). In the diptych, Mackiewicz studies the city as a strictly urban space without reference to tradition or cultural and symbolic imagery. Observations and descriptions of the everyday life of pre-war Vilnius gave rise to texts in which motifs specific to urban literature appear, such as the movement and rhythm of urban life, the organisation of time, or the peculiarities of the audiosphere. The protagonist-narrator of these texts also resides in the city in a modern way: he focuses on empiricism and the sensory-bodily perception of the city. On the other hand, the reportage series belongs to the non-fiction literature of the 1930s. Some of Mackiewicz's pre-war works, including the analysed series, belong to the period of literature’s turn towards social issues, when the life of the lower classes, especially in the metropolis’s suburbs, gained its literary and journalistic representations. The analysed series about suburbs discovered new anthropological spaces, alternative to the time’s literary representations, and modified existing ideas about Vilnius.
Keywords: Józef Mackiewicz; Vilnius; urban space; report; essay